Peranan Dewan Pendidikan Dalam Pelaksanaan Kebijakan Pendidikan Di Kota Palopo - Saputra, Aco Nata (Jurnal Arajang, 2022)
Consist of research objectives, methods, result or findings , conclusion and limitation (optional). This study aims to determine the role of the city's Education Council in implementing educational policies in the city of Palopo. To find out what factors influence the role of the city's Education Council in implementing education policies in the city of Palopo. The results of this research are expected to be input for the Palopo city government and the Palopo city education council, to provide even better service to the community, especially education issues, and the results of this research are expected to provide added value which can then be compared with other scientific studies. , especially those that examine the issue of Education Policy. The type of research used is descriptive research type, namely a study that aims to provide an overview or explanation of the role of the city's Board of Education in the implementation of education policy in the city of Palopo. Qualitatively analyzed both quantitative and qualitative data based on reports and records in the field. With data collection techniques library research (library research) and field studies (field research), namely observation and interviews. From the results of this study it can be shown that the role played by the Education Council in implementing the Education Policy of the Palopo city government is a standard rule set by the central government, while the role of the Palopo City Education Council is as follows: Advisory agency in determining and educational policy, Supporting agency, both in the form of financial, thinking and energy in implementing education, Controlling agency in the framework of transparency and accountability in the implementation of educational output, Mediator between the government (executive) and the regional people's representative council (DPRD (legislative) ) with society.